Multi-component copolymerized thickening agent for fracturing and preparation method of multi-component copolymerized thickening agent

The composite polymer thickening agent prepared by copolymerizing hydrotalcite with phenyl-containing monomers, etc., solves the problem of insufficient stability and salt resistance of the existing thickening agent in high temperature and high mineralization environments, and realizes the thermal stability, viscosity maintenance and mechanical shear stability of the thickening agent, and is suitable for unconventional oil and gas reservoirs.

CN119842029AInactive Publication Date: 2025-04-18LUOYANG YUSHENG CHEMICAL CO LTD +1

Patent Information

Application Number
CN202510319287.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-18
Publication Date
2025-04-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing thickener for fracturing fluid has poor thermal stability, reduced viscosity, insufficient salt resistance and structural damage during mechanical shearing in high temperature and high mineralization environments, resulting in poor application effect in complex unconventional oil and gas reservoir environments.

Method used

By copolymerizing modified hydrotalcite, phenyl-containing monomer, acrylamide matrix and functional monomer, a composite polymer thickening agent is prepared, and the thickening, salt resistance and mechanical shear stability of the thickening agent are improved through specific preparation steps and conditions.

Benefits of technology

The thermal stability and viscosity maintenance of the thickener in high temperature and high mineralization environments is achieved, and its salt resistance and mechanical shear stability are enhanced. It is suitable for complex unconventional oil and gas reservoir environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention belongs to the field of thickening agents, and particularly relates to a multi-component copolymerization thickening agent for fracturing and a preparation method of the multi-component copolymerization thickening agent for fracturing. The preparation method comprises the following steps: reacting acryloyl chloride with 4-(p-hydroxyphenyl)-2-butanol to prepare a phenyl-containing monomer; copolymerizing the modified hydrotalcite, a phenyl-containing monomer, a matrix and a functional monomer to obtain a composite polymer; and drying and crushing the composite polymer to obtain the multi-component copolymerization thickening agent for fracturing. The thickening property and the salt resistance of the multi-component copolymerized thickening agent for fracturing are obviously improved, and the multi-component copolymerized thickening agent for fracturing is high in stability at high temperature and under mechanical shearing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of thickeners, and in particular relates to a multi-component copolymer thickener for fracturing and a preparation method thereof. Background Art

[0002] Thickeners for fracturing fluid mainly include natural plant gums and their derivatives, cellulose derivatives and synthetic polymers. The natural plant gums and their derivatives used at home and abroad are mainly guar gum and modified guar gum derivatives. With the increase in the depth of reservoir development, guar gum fracturing fluid thickeners face the problem of high temperature thermal degradation and difficulty in breaking the gel. The residue content of such thickeners is high, which will cause damage to oil and gas reservoirs. Cellulose derivatives are also a common water-based fracturing fluid thickener. However, cellulose derivative thickeners also have problems such as poor solubility, poor thermal stability, salt intolerance, and high content of broken gel residues, and cannot be widely used. Synthetic polymer thickeners have the advantages of good viscoelasticity, temperature resistance, easy breaking of gel, less residue and less damage to the formation. In recent years, they have become a hot topic of research at home and abroad. However, the environment of unconventional oil and gas reservoirs is relatively complex, and the fracturing fluids used therein have the following problems: most reservoirs have high temperatures and the formation water contains a large amount of electrolytes and high mineralization. High temperature will hydrolyze the amide group of the polymer thickener, destroy the network structure of the fracturing fluid, and reduce the viscosity. Formation water contains a large amount of sodium, magnesium, calcium and other ions, which will weaken the hydration of polymers and weaken their thickening ability. Whether it is natural polymers or synthetic polymer thickeners, it is difficult to dissolve at high mineralization. In addition, during the hydraulic fracturing process, the fracturing fluid is often subjected to mechanical shearing from the fracturing pump, wellbore, and porous media, causing the polymer molecular chain to break, the network structure to be destroyed, and the viscosity to decrease. Summary of the invention

[0003] The present invention mainly provides a method for preparing a multi-component copolymer thickener for fracturing with good thermal stability, high viscosity and salt resistance, and the thickener prepared by the method. The technical scheme is as follows: A method for preparing a multi-component copolymer thickener for fracturing comprises the following steps: modifying hydrotalcite to obtain modified hydrotalcite; using acryloyl chloride and 4-(p-hydroxyphenyl)-2-butanol to react to prepare a phenyl-containing monomer; copolymerizing the modified hydrotalcite, the phenyl-containing monomer, an acrylamide matrix and a functional monomer to obtain a composite polymer; and drying and crushing the composite polymer to obtain a multi-component copolymer thickener for fracturing.

[0004] Furthermore, the mass of the modified hydrotalcite is 1-5% of the acrylamide matrix; the mass of the phenyl-containing monomer is 2-10% of the acrylamide matrix; and the mass ratio of the functional monomer to the acrylamide matrix is ​​0.2-0.6:1.

[0005] Furthermore, the method comprises the following steps: weighing a phenyl-containing monomer, an acrylamide matrix and a functional monomer, placing them in water, and mixing them evenly to obtain a mixed monomer solution; adjusting the pH value of the mixed monomer solution to 8-11, placing the modified hydrotalcite in the mixed monomer solution and fully dispersing them, deoxygenating them with nitrogen, adding ammonium persulfate and sodium bisulfite initiators, reacting them at 25-35° C. under the protection of nitrogen for 4-6 hours to obtain a gel product; purifying the gel product, drying it, and crushing it to obtain a multi-component copolymer thickener for fracturing.

[0006] Furthermore, the mass ratio of ammonium persulfate to sodium bisulfite is 2:1; the mass of the initiator accounts for 0.18-0.35% of the total mass of the phenyl-containing monomer and the functional monomer; the gel product is purified and placed in anhydrous methanol for dehydration and drying, and then dried at 40-60° C. and ground.

[0007] Further, the preparation of the modified hydrotalcite comprises the following steps: a. Weigh 0.2g of hydrotalcite and place it in an ethanol aqueous solution, fully disperse it to obtain a hydrotalcite dispersion; place γ-aminopropyltriethoxysilane in ethanol to obtain a γ-aminopropyltriethoxysilane solution; then drop the γ-aminopropyltriethoxysilane solution into the hydrotalcite dispersion, stir and react for 2-4h; separate and collect the precipitate, wash it fully, and then vacuum dry it to obtain a primary modified hydrotalcite; b. Dissolve phenol in an aqueous solution of ethanol at room temperature to prepare a saturated phenol solution, place the primary modified hydrotalcite in the saturated phenol solution, fully disperse it, and pretreat it for 1 to 2 hours to obtain an activated modified hydrotalcite mixed solution; c. Place sodium dodecyl sulfate in the activated modified hydrotalcite mixture, fully disperse it and let it stand for 4-6 hours; separate and collect the precipitate, rinse it with ethanol, and dry it to obtain the modified hydrotalcite.

[0008] Furthermore, the concentration of ethanol in the ethanol aqueous solution in step a is 25-40% v / v; and the mass ratio of the hydrotalcite to γ-aminopropyltriethoxysilane is 1:10-20.

[0009] Furthermore, the concentration of ethanol in the ethanol aqueous solution in step b is 50-70% v / v; the pretreatment temperature is 40-55° C.; and the mass ratio of the primary modified hydrotalcite to sodium dodecyl sulfate is 1:0.3-0.8.

[0010] Further, the preparation of the phenyl-containing monomer comprises the following steps: Dissolve 4-(p-hydroxyphenyl)-2-butanol and triethylamine in dichloromethane to obtain a mixed solution with a concentration of 0.1-0.15 g / mL of 4-(p-hydroxyphenyl)-2-butanol; prepare a dichloromethane solution of 0.1-0.2 g / mL of acryloyl chloride, slowly drip the dichloromethane solution of acryloyl chloride into the mixed solution at low temperature in the dark, place it in a room temperature environment to naturally heat up and continue to react in the dark for 4-6 hours; take the upper filtrate, wash it thoroughly after rotary evaporation, and dry it with anhydrous sodium sulfate to obtain a phenyl-containing monomer.

[0011] Furthermore, the mass ratio of the 4-(p-hydroxyphenyl)-2-butanol to acryloyl chloride is 1.6-2:1; the mass ratio of the triethylamine to acryloyl chloride is 2-2.5:1; the low temperature is -10-5°C; and the slow dripping speed is 0.5-1.5 mL / min.

[0012] A multi-component copolymer thickener for fracturing prepared by the above method, wherein the functional monomers include one or more of 2-methyl-2-acrylamidopropanesulfonic acid, vinylsulfonic acid, vinylbenzenesulfonic acid, octadecyl methacrylate, alkyl polyoxyethylene methacrylate, dimethyloctadecyl allyl ammonium chloride, dimethylbehenyl allyl ammonium chloride, dimethyltetradecyl (2-acrylamidopropyl) ammonium bromide, N,N-dimethylacrylamide, acrylic acid, and styrene.

[0013] By adopting the above scheme, the method of the present invention has the following advantages: 1. The present invention copolymerizes modified hydrotalcite, phenyl-containing monomers, acrylamide matrix and functional monomers to obtain a thickener with significantly improved thickening and salt resistance, and strong stability under high temperature and mechanical shearing.

[0014] 2. The present invention modifies the hydrotalcite so that a large number of organic functional groups are generated on the surface of the hydrotalcite, thereby improving the affinity between the hydrotalcite and the polymer, allowing the hydrotalcite to be fully dispersed in the polymer and avoiding the aggregation of inorganic particles.

[0015] 3. The present invention uses sodium dodecyl sulfate as an intercalant, which enters the interlayer of hydrotalcite through ion exchange, improves the adsorption of hydrotalcite, facilitates the insertion of polymer into the interlayer of hydrotalcite, fully combines with hydrotalcite, facilitates the uniform dispersion of hydrotalcite, and improves the stability of the thickener.

[0016] 4. In the present invention, during the polymerization process of the thickener monomer, the modified hydrotalcite is directly added, the hydrotalcite particles are evenly dispersed in the polymer monomer, the monomer is polymerized in the nanoparticles and between the particles, and the grafted coupling agent is entangled and crossed with the polymer chain, making the polymer more shear-resistant, and the anions introduced by the hydrotalcite can react with -COO - The groups form protection and improve the salt resistance of the thickener.

[0017] 5. The present invention introduces hydroxyl groups and phenyl groups into the polymer monomers. The hydroxyl groups can form electrostatic attraction with the cross-linking agent, thereby improving the cross-linking efficiency, and to a greater extent, increasing the viscosity of the system and the stability of the fracturing fluid gel. In addition, the present invention can capture oxygen free radicals formed by oxygen fission under high temperature conditions, thereby improving the high temperature resistance of the thickener.

[0018] 6. The introduction of phenyl groups into the thickener of the present invention can enhance the steric effect of the side groups and increase the hydrodynamic volume of the polymer molecular chain in the solution, thereby increasing the viscosity of the fracturing fluid.

[0019] 7. The preparation method of the present invention is simple, and the obtained thickener has high viscosity, high thermal decomposition temperature, and strong stability. It is an efficient thickener with excellent temperature resistance, salt resistance, and shear resistance, and is suitable for oil field fracturing. DETAILED DESCRIPTION

[0020] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0021] Example 1: (1) Weigh 1 g of magnesium aluminum hydrotalcite and place it in an aqueous solution of ethanol with a concentration of 30% v / v, and fully disperse it to obtain a hydrotalcite dispersion; place 20 g of γ-aminopropyltriethoxysilane in ethanol to obtain a γ-aminopropyltriethoxysilane solution; then dropwise add the γ-aminopropyltriethoxysilane solution to the hydrotalcite dispersion, and stir to react for 4 hours; separate and collect the precipitate, wash it thoroughly, and then vacuum dry it to obtain a primary modified hydrotalcite; (2) dissolving phenol in an aqueous solution of ethanol at a concentration of 70% v / v at room temperature to prepare a phenol saturated solution, placing 1 g of the primary modified hydrotalcite in the phenol saturated solution, and after fully dispersing, pretreating at 40°C for 1 to 2 h to obtain an activated modified hydrotalcite mixed solution; (3) 0.8 g of sodium dodecyl sulfate was placed in the activated modified hydrotalcite mixture, fully dispersed and allowed to stand for 6 h; the precipitate was separated and collected, washed with ethanol, and dried to obtain the modified hydrotalcite; (4) Dissolve 3.5 g of 4-(p-hydroxyphenyl)-2-butanol and 2 g of triethylamine in 30 mL of dichloromethane to obtain a mixed solution; dissolve 1 g of acryloyl chloride in 12 mL of dichloromethane to obtain a dichloromethane solution of acryloyl chloride; drip the dichloromethane solution of acryloyl chloride into the mixed solution at a rate of 0.5 mL / min at 0°C in the dark. After the dripping is completed, place the mixture in a room temperature environment to naturally heat up and continue to react in the dark for 6 hours; take the upper filtrate and wash it thoroughly after rotary evaporation, and dry it over anhydrous sodium sulfate to obtain a phenyl-containing monomer; (5) Weigh acrylamide matrix, acrylic acid and 2-methyl-2-acrylamidopropanesulfonic acid in a mass ratio of 1:0.3:0.08, and then take 6% of the mass of phenyl-containing monomer of acrylamide matrix and put them in water, mix them evenly, and obtain a mixed monomer solution; use 10% of sodium hydroxide to adjust the pH value of the mixed monomer solution to 9, and put 3% of the mass of modified hydrotalcite of acrylamide matrix into the mixed monomer solution to fully disperse; after nitrogen is passed through to deoxygenate, add 0.3% of ammonium persulfate and sodium bisulfite initiators in a mass ratio of 2:1 based on the total mass of phenyl-containing monomer and 2-methyl-2-acrylamidopropanesulfonic acid, and react at 30-35°C under the protection of nitrogen for 5 hours to obtain a gel product; put the gel product in acetone, repeat precipitation and separation for many times, and after sufficient purification, put it in anhydrous methanol to remove water and dry, and then dry it at 50°C and crush it to obtain a multi-component copolymer thickener for fracturing.

[0022] Embodiment 2: The difference from Embodiment 1 is that: (1) Weigh 1 g of magnesium aluminum hydrotalcite and place it in an aqueous solution of ethanol with a concentration of 30% v / v, and fully disperse it to obtain a hydrotalcite dispersion; place 10 g of γ-aminopropyltriethoxysilane in ethanol to obtain a γ-aminopropyltriethoxysilane solution; then add the γ-aminopropyltriethoxysilane solution dropwise to the hydrotalcite dispersion, and stir to react for 4 hours; separate and collect the precipitate, wash it thoroughly, and then vacuum dry it to obtain a primary modified hydrotalcite.

[0023] Embodiment 3: The difference from Embodiment 1 is that: (1) Weigh 1 g of magnesium aluminum hydrotalcite and place it in an aqueous solution of ethanol with a concentration of 30% v / v, and fully disperse it to obtain a hydrotalcite dispersion; place 20 g of γ-aminopropyltriethoxysilane in ethanol to obtain a γ-aminopropyltriethoxysilane solution; then drop the γ-aminopropyltriethoxysilane solution into the hydrotalcite dispersion, and stir to react for 2 h; separate and collect the precipitate, wash it thoroughly, and then vacuum dry it to obtain a primary modified hydrotalcite.

[0024] Embodiment 4: The difference from Embodiment 1 is that: (2) Phenol was dissolved in an aqueous solution of ethanol at a concentration of 50% v / v at room temperature to prepare a saturated phenol solution. 1 g of the primary modified hydrotalcite was placed in the saturated phenol solution and, after being fully dispersed, was pretreated at 40°C for 1 to 2 h to obtain an activated modified hydrotalcite mixed solution.

[0025] Embodiment 5: The difference from Embodiment 1 is that: (2) Phenol was dissolved in an aqueous solution of ethanol at a concentration of 70% v / v at room temperature to prepare a saturated phenol solution. 1 g of the primary modified hydrotalcite was placed in the saturated phenol solution and, after being fully dispersed, was pretreated at 55°C for 1 to 2 h to obtain an activated modified hydrotalcite mixed solution.

[0026] Embodiment 6: The difference from Embodiment 1 is that: (3) 0.3 g of sodium dodecyl sulfate was placed in the activated modified hydrotalcite mixture, fully dispersed and allowed to stand for 6 h; the precipitate was separated and collected, washed with ethanol, and dried to obtain the modified hydrotalcite.

[0027] Embodiment 7: The difference from Embodiment 1 is that: (3) 0.8 g of sodium dodecyl sulfate was placed in the activated modified hydrotalcite mixture, fully dispersed and allowed to stand for 4 h; the precipitate was separated and collected, washed with ethanol, and dried to obtain the modified hydrotalcite.

[0028] Embodiment 8: The difference from Embodiment 1 is that: (4) Dissolve 3.5 g of 4-(p-hydroxyphenyl)-2-butanol and 2 g of triethylamine in 30 mL of dichloromethane to obtain a mixed solution; dissolve 1 g of acryloyl chloride in 12 mL of dichloromethane to obtain a dichloromethane solution of acryloyl chloride; drip the dichloromethane solution of acryloyl chloride into the mixed solution at a rate of 0.5 mL / min at 5°C in the dark. After the dripping is completed, place the mixture in a room temperature environment to naturally heat up and continue to react in the dark for 6 hours; take the upper filtrate, evaporate it, wash it thoroughly, and dry it with anhydrous sodium sulfate to obtain a phenyl-containing monomer.

[0029] Embodiment 9: The difference from Embodiment 1 is that: (4) Dissolve 3.5 g of 4-(p-hydroxyphenyl)-2-butanol and 2 g of triethylamine in 30 mL of dichloromethane to obtain a mixed solution; dissolve 1 g of acryloyl chloride in 12 mL of dichloromethane to obtain a dichloromethane solution of acryloyl chloride; drip the dichloromethane solution of acryloyl chloride into the mixed solution at a rate of 1.5 mL / min at 0°C in the dark. After the dripping is completed, place the mixture in a room temperature environment to naturally heat up and continue to react in the dark for 6 hours; take the upper filtrate and wash it thoroughly by rotary evaporation, and dry it with anhydrous sodium sulfate to obtain a phenyl-containing monomer.

[0030] Embodiment 10: The difference from Embodiment 1 is that: (4) Dissolve 3.5 g of 4-(p-hydroxyphenyl)-2-butanol and 2 g of triethylamine in 30 mL of dichloromethane to obtain a mixed solution; dissolve 1 g of acryloyl chloride in 12 mL of dichloromethane to obtain a dichloromethane solution of acryloyl chloride; drip the dichloromethane solution of acryloyl chloride into the mixed solution at a rate of 0.5 mL / min at 0°C in the dark. After the dripping is completed, place the mixture in a room temperature environment to naturally heat up and continue to react in the dark for 4 hours; take the upper filtrate, evaporate it, wash it thoroughly, and dry it with anhydrous sodium sulfate to obtain a phenyl-containing monomer.

[0031] Embodiment 11: The difference from Embodiment 1 is that: (5) Weigh acrylamide matrix, acrylic acid and 2-methyl-2-acrylamidopropanesulfonic acid in a mass ratio of 1:0.3:0.08, and then take phenyl-containing monomers accounting for 2% of the mass of acrylamide matrix and put them in water, mix them evenly, and obtain a mixed monomer solution; use 10% sodium hydroxide to adjust the pH value of the mixed monomer solution to 9, and put 3% of the mass of modified hydrotalcite in the mixed monomer solution to fully disperse; after nitrogen is passed through to deoxygenate, add 0.3% of ammonium persulfate and sodium bisulfite initiators accounting for the total mass of phenyl-containing monomers and 2-methyl-2-acrylamidopropanesulfonic acid in a mass ratio of 2:1, react at 30-35°C under the protection of nitrogen for 5 hours, and obtain a gel product; put the gel product in acetone, repeat precipitation and separation for many times, and after sufficient purification, put it in anhydrous methanol to remove water and dry, and then dry it at 50°C and crush it to obtain a multi-component copolymer thickener for fracturing.

[0032] Embodiment 12: The difference from Embodiment 1 is that: (5) Weigh acrylamide matrix, acrylic acid and 2-methyl-2-acrylamidopropanesulfonic acid in a mass ratio of 1:0.3:0.08, and then take 6% of the mass of the acrylamide matrix and put it in water, mix them evenly, and obtain a mixed monomer solution; use 10% of sodium hydroxide to adjust the pH value of the mixed monomer solution to 9, and put 1% of the mass of the acrylamide matrix into the mixed monomer solution to fully disperse; after nitrogen is passed through to deoxygenate, add 0.3% of ammonium persulfate and sodium bisulfite initiators in a mass ratio of 2:1 based on the total mass of the phenyl-containing monomer and 2-methyl-2-acrylamidopropanesulfonic acid, and react at 30-35°C under the protection of nitrogen for 5 hours to obtain a gel product; put the gel product in acetone, repeat precipitation and separation for many times, and after sufficient purification, put it in anhydrous methanol to remove water and dry, and then dry it at 50°C and crush it to obtain a multi-component copolymer thickener for fracturing.

[0033] Example sample test: The thickener of each example was prepared into a thickener solution with a mass fraction of 0.3%, and 0.3% hexamethylenetetramine was added to prepare a gel. -1 The viscosity of the fracturing fluid gel was tested at a shear rate of 600s to evaluate the shear resistance. -1 The viscosity of the fracturing fluid gel was measured at a shear rate of 140°C to evaluate the temperature resistance. Another gel was prepared to test the viscosity of the fracturing fluid gel after salt treatment with calcium chloride with a mass fraction of 5 g / L to evaluate the salt resistance. The results are shown in Table 1: Table 1: Properties of samples in various embodiments:

[0034] Compared with Example 1, Example 2 adds less coupling agent in the process of hydrotalcite modification, but the viscosity of the prepared gel after high-speed shear and high-temperature treatment is higher than that of Example 1, indicating that its shear resistance is better, while the viscosity of Example 3 with a shorter crosslinking time is not as good as that of Example 1, indicating that more sufficient crosslinking is conducive to improving the affinity of hydrotalcite and polymer and improving the stability of the polymer structure, but too much coupling agent is easy to form a multilayer coating on the surface of hydrotalcite, which will reduce the interfacial adhesion between particles and the resin matrix, and weaken the stability of the structure. When pre-treating the primary modified hydrotalcite, the ethanol content in the phenol solvent of Example 4 is less, and the phenol content is relatively less, which is insufficient for the activation degree of the primary modified hydrotalcite, while the temperature of the later heating of Example 5 is higher, and the amount of phenol involved in the reaction is also more, which is easy to affect the structure of the hydrotalcite, so the stability of Examples 4 and 5 is not as good as that of Example 1, and the viscosity is reduced. When modifying the hydrotalcite, less intercalating agent was added in Example 6, and the standing time in Example 7 was shorter. The viscosities of Examples 6 and 7 after high-speed shear and high-temperature treatment were lower, especially the viscosity of the gel decreased significantly after salt treatment, indicating that the anions introduced by the hydrotalcite are beneficial to improving the salt resistance of the thickener.

[0035] When preparing the phenyl-containing monomer, compared with Example 1, Example 8 has a higher temperature when mixing the raw materials, Example 9 has a faster dropping speed, and Example 10 has a shorter reaction time. The shear resistance of the samples of Examples 8 to 10 is significantly reduced, and violent reactions and insufficient reactions will affect the purity of the phenyl-containing monomer, indicating that the phenyl-containing monomer prepared by the present invention has a significant improvement effect on the mechanical properties of the thickener. In Example 11, less phenyl-containing monomers are added during the polymerization process, and the viscosity of the sample after the shear resistance test is significantly reduced; in Example 12, the amount of modified hydrotalcite added is small, and the viscosity of the sample after the salt resistance test is significantly reduced. In addition, all the properties of the samples of Examples 11 and 12 are reduced to varying degrees, indicating that the components in the thickener of the present invention can significantly improve the shear resistance, temperature resistance and salt resistance of the thickener, and it can be seen from the degree of viscosity reduction that a single increase or decrease in the content of the modified hydrotalcite or phenyl-containing monomer of the present invention has a significant effect on the performance of the thickener, and the content of the modified hydrotalcite or phenyl-containing monomer needs to be controlled within a suitable proportional relationship.

[0036] For those skilled in the art, various other corresponding changes and deformations can be made according to the technical solutions and concepts described above, and all of these changes and deformations should fall within the protection scope of the claims of the present invention.

Claims

1. A method for preparing a multi-component copolymer thickener for fracturing, characterized in that: The hydrotalcite is modified to obtain a modified hydrotalcite; acryloyl chloride and 4-(p-hydroxyphenyl)-2-butanol are reacted to prepare a phenyl-containing monomer; the modified hydrotalcite, the phenyl-containing monomer, an acrylamide matrix and a functional monomer are copolymerized to obtain a composite polymer; and the composite polymer is dried and crushed to obtain a multi-polymer thickener for fracturing.

2. The method for preparing a multi-component copolymer thickener for fracturing according to claim 1, characterized in that: The mass of the modified hydrotalcite is 1-5% of the acrylamide matrix; the mass of the phenyl-containing monomer is 2-10% of the acrylamide matrix; and the mass ratio of the functional monomer to the acrylamide matrix is ​​0.2-0.6:

1.

3. The method for preparing a multi-component copolymer thickener for fracturing according to claim 1, characterized in that: The following steps are involved: Weigh a phenyl-containing monomer, an acrylamide matrix and a functional monomer, put them in water, mix them evenly, and obtain a mixed monomer solution; adjust the pH value of the mixed monomer solution to 8-11, put the modified hydrotalcite in the mixed monomer solution and fully disperse it, pass nitrogen to deoxygenate, add ammonium persulfate and sodium bisulfite initiators, react at 25-35° C. under the protection of nitrogen for 4-6 hours, and obtain a gel product; The gel product is purified, dried and crushed to obtain a multi-polymer thickener for fracturing.

4. The method for preparing a multi-component copolymer thickener for fracturing according to claim 3, characterized in that: The mass ratio of ammonium persulfate to sodium bisulfite is 2:1; the mass of the initiator accounts for 0.18-0.35% of the total mass of the phenyl-containing monomer and the functional monomer; the gel product is purified and placed in anhydrous methanol for dehydration and drying, and then dried at 40-60° C. and ground.

5. The method for preparing a multi-component copolymer thickener for fracturing according to claim 1, characterized in that: The preparation of modified hydrotalcite comprises the following steps: a. Weigh 0.2g of hydrotalcite and place it in an ethanol aqueous solution, fully disperse it to obtain a hydrotalcite dispersion; place γ-aminopropyltriethoxysilane in ethanol to obtain a γ-aminopropyltriethoxysilane solution; then drop the γ-aminopropyltriethoxysilane solution into the hydrotalcite dispersion, stir and react for 2-4h; separate and collect the precipitate, wash it fully, and then vacuum dry it to obtain a primary modified hydrotalcite; b. Dissolve phenol in an aqueous solution of ethanol at room temperature to prepare a saturated phenol solution, place the primary modified hydrotalcite in the saturated phenol solution, fully disperse it, and pretreat it for 1 to 2 hours to obtain an activated modified hydrotalcite mixed solution; c. Place sodium dodecyl sulfate in the activated modified hydrotalcite mixture, fully disperse it and let it stand for 4-6 hours; separate and collect the precipitate, rinse it with ethanol, and dry it to obtain the modified hydrotalcite.

6. The method for preparing a multi-component copolymer thickener for fracturing according to claim 5, characterized in that: The concentration of ethanol in the ethanol aqueous solution in step a is 25-40% v / v; the mass ratio of the hydrotalcite to γ-aminopropyltriethoxysilane is 1:10-20.

7. The method for preparing a multi-component copolymer thickener for fracturing according to claim 5, characterized in that: In step b, the concentration of ethanol in the ethanol aqueous solution is 50-70% v / v; the pretreatment temperature is 40-55° C.; and the mass ratio of the primary modified hydrotalcite to sodium dodecyl sulfate is 1:0.3-0.

8.

8. The method for preparing a multi-component copolymer thickener for fracturing according to claim 1, characterized in that: The preparation of the phenyl-containing monomer comprises the following steps: Dissolve 4-(p-hydroxyphenyl)-2-butanol and triethylamine in dichloromethane to obtain a mixed solution with a concentration of 0.1-0.15 g / mL of 4-(p-hydroxyphenyl)-2-butanol; prepare a dichloromethane solution of 0.1-0.2 g / mL of acryloyl chloride, slowly drip the dichloromethane solution of acryloyl chloride into the mixed solution at low temperature in the dark, place it in a room temperature environment to naturally heat up and continue to react in the dark for 4-6 hours; take the upper filtrate, wash it thoroughly after rotary evaporation, and dry it with anhydrous sodium sulfate to obtain a phenyl-containing monomer.

9. The method for preparing a multi-component copolymer thickener for fracturing according to claim 8, characterized in that: The mass ratio of the 4-(p-hydroxyphenyl)-2-butanol to acryloyl chloride is 1.6-2:1; the mass ratio of the triethylamine to acryloyl chloride is 2-2.5:1; the low temperature is -10-5°C; and the slow dripping speed is 0.5-1.5 mL / min.

10. A multi-component copolymer thickener for fracturing prepared by the method according to any one of claims 1 to 9, characterized in that: The functional monomers include one or more of 2-methyl-2-acrylamidopropanesulfonic acid, vinylsulfonic acid, vinylbenzenesulfonic acid, octadecyl methacrylate, alkyl polyoxyethylene methacrylate, dimethyloctadecyl allyl ammonium chloride, dimethylbehenyl allyl ammonium chloride, dimethyltetradecyl (2-acrylamidopropyl) ammonium bromide, N,N-dimethylacrylamide, acrylic acid, and styrene.

Citation Information

Patent Citations

  • Amphoteric ionic polymer water base fracturing fluid thickening agent and preparation method thereof

    CN103131404A

  • Curable resin composition, cured product thereof and printed circuit board using same

    CN103459504A

  • Preparation method of polyacrylamide nano composite fracturing fluid

    CN104109525A

  • Temperature-resistant polyacrylamide fracturing fluid thickening tackifier and preparation method thereof

    CN117736370A

  • High-salt-resistant and high-temperature-resistant instant associative thickening agent for fracturing and preparation method thereof

    CN118496448A

Cited By

  • Butter packaging composite film and preparation method thereof

    CN120439650A